Dielectrophoresis-based microfluidic device for separation of potential cancer cells - Nur Fatien Najwa Mohamad Narji; Mohd Ridzuan Ahmad (Bulletin of Electrical Engineering and Informatics, 2020)
Cancer is a leading cause of death that adversely affects all ages and genders around the world. There is a range of approaches such as CT scanning and mammography to diagnose cancer. Although the current method has many benefits, most of it share similar drawbacks as the result of detection takes long time and can lead to over diagnosis. Dielectrophoresis (DEP) is a method that can be used to obtain the cell electrical properties such as capacitance, conductivity, and permittivity. A device was designed in this study using a pair of electrodes and main channel with two inlets and two outlets. COMSOL software is adopted to analyze channel particle flow. Results show the configuration of microfluidic device and its dimensions. For potential application, DEP may be used as a non-invasive technique to distinguish normal cell from cancerous cell, which can lead to early detection as it offers a real-time warning. The simulations reveal that the electrodes captured the particles successfully and sorted them within specific time. The chance of cell capture and the ability of the electrodes to sort the cells is around 80%. In addition, an ideal design of the microfluidic chip was established, incorporating the cell and dielectric properties.